An audit of antenatal education facilitated by physiotherapists in Western Australian public hospitals - Wilson, J.; Berlach, R.; Hill, Anne-Marie (2014)
This paper reports on the delivery of antenatal education by physiotherapists in Western Australia in 2012, including the location of antenatal education providers, number of mothers attending, qualifications of physiotherapists involved, allocation of physiotherapy hours, the content of the education, and strategies used to enhance learning in the classes. A survey was emailed to the physiotherapists in 31 hospitals with maternity services that were funded by the Department of Health Western Australia. Antenatal education facilitated by a physiotherapist was provided at 25/30 (83.3%) hospitals. Four physiotherapists had postgraduate women's health qualifications and all the antenatal education classes provided information about pelvic floor muscle exercises. There was a wide variation in pelvic floor muscle exercise prescription. Fewer than 50% of first-time mothers who give birth in the public sector have attended physiotherapy facilitated antenatal education classes.